PENGARUH SKEPTISME PROFESIONAL, PENGALAMAN KERJA, AUDIT FEE DAN INDEPENDENSI TERHADAP KUALITAS AUDIT PADA KAP DI DKI JAKARTA - Susi Dwi Mulyani; Jimmi Osamara Munthe (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The purpose of this study was to determine the Influence of Professional Skeptism, Work Experience, Audit Fee and Independence to Audit Quality at Public Accountants in DKI Jakarta. The data used in this study are the primary data in the form of a respondent's answers from questionnaire data collection. Sample taking use a coevicience sampling method were 150 samples that meet the criteria. This study used multiple linear regression analysis for hypothesis test. The results showed variable professional skepticism and audit fees that have positive effect on audit quality and work experience variables and independence not have influences audit quality.